Early detection of Alzheimer's disease using the MEMORIES mnemonic - Valentinus Besin; Farizky M. Humardani (Chronic Diseases and Translational Medicine)
Abstract The rising incidence and death rates linked to Alzheimer's disease (AD) highlight an urgent issue. Genetic screening is celebrated as a significant advancement for its early detection capabilities, pinpointing those at risk before the emergence of symptoms. Yet, the limited availability of these technologies highlights a critical gap in widespread application. This review pivots to the potential of presymptomatic clinical assessments as a readily available, economical, and simple strategy for early detection. Traditionally, AD diagnosis relies on the late‐stage identification of cognitive deterioration, functional impairments, and neuropsychiatric symptoms, coinciding with advanced brain degeneration. Conversely, emerging research identifies early indicators preceding significant degeneration, manifesting years before clinical symptoms. We introduce a mnemonic, MEMORIES, to categorize these prodromal: Metabolism changes, Eye/visual impairments, March (refer to gait disturbances), Olfactory dysfunction, Rhythm (blood pressure and heart rate), Insensitivity of the tongue, Ears (hearing loss), and Stool alterations. Recognizing these prodromal through clinical examinations provides a valuable strategy for initiating preventative actions against brain degeneration. This approach advocates for broadening the screening lens beyond genetic screening to encompass clinical evaluations, enhancing early detection and intervention opportunities for AD.